Attitudes to Hand Hygiene Performance among Nursing Staff during Covid-19 Pandemic - Mohammed Hindi Alwatifi, Wafaa Abd Ali Hattab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proper hand hygiene was identified as one of the simplest most cost-effective Covid-19 prevention measures. However, there is no available evidence indicating that hand hygiene is fully practiced by health care workers Objectives: This study aimed to fill this gap by assessing the attitudes regarding hand hygiene practice among nursing staff during the Covid-19 pandemic Methodology: A descriptive cross-sectional design was carried out in three hospitals’ Intensive Care Units from the period (20th December 2021 to 30th January 2022). A non-probability sampling method consists of (130) nurses who were selected purposively based on the study criteria Results: The majority of the study participants (73.1%) had negative attitudes towards hand hygiene. Conclusion: There were an overall high proportion of participants with negative attitudes level toward hand hygiene.